Prevalence and Association of Helicobacter pylori Infection in Gastric Disease at Dr. Cipto Mangunkusumo General National Hospital 2010–2021 - Marcellus Simadibrata; Dewi Mustikarani (The Indonesian Journal of Gastroenterology, Hepatology and Digestive Endoscopy)
Background: Several studies showed contrasting associations between Helicobacter pylori infection and organic gastric disorders. We aim to determine the association between H. pylori infection and gastroesophageal reflux disease (GERD), gastric polyp, and gastric cancer in an Indonesian national referral hospital.